Investigation of rubella vaccine maked MICROGEN Federal State Company: study I trial - A. N. Mironov; A. A. Tsaan; D. S. Bushmenkov; A. A. Romanova; Ye. S. Sidorenko; I. V. Feldblum (Бюллетень сибирской медицины, 2011)
Experts of the RPU «Microgene», developed the new domestic medication for prevention of rubella — The rubella vaccine cultural live, on the basis of the vaccine strain RA 27/3. After the safety of vaccine had been proved on laboratory animals, the clinical trial had been activated on volunteers.The first phase of trial had been carried out on the women at the age of 18—25.After introduction of medications (vaccine or production strain of vaccine) the volunteers had been observed during 42 days. Blood and urine sampling had been executed till vaccination and 28 days later after introduction of medications.Results of trial presented safety, low reactogenicity and evident immunologic properties of medications. It permitted to start the next phase of the clinical trial on the basis of children’s volunteers.